ANALYSIS OF USER SATISFACTION ON THE IMPLEMENTATION OF CRM, TQM AND SERVICE QUALITY (Case Study of UNIKI Bireuen Library Users – Aceh Province) - Fadhliah, Laina; Malik, Imam; Musrizal, Musrizal (IndOmera, 2025)
This study aims to analyze factors related to user satisfaction of UNIKI campus library, by limiting it to CRM, TQM and service quality factors. Data sources were obtained through questionnaires to users, namely 275 students who use UPT Library services, using quantitative-associative methods and problem analysis tools with path analysis models. The results of the study obtained information that: (1) the implementation of CRM has a direct and indirect effect on user satisfaction of 35.32%, while the implementation of TQM is 51.57% and the service quality aspect is quite significant at 45.58%. (2) Simultaneously, the implementation of CRM, TQM and service quality provide a positive contribution to user satisfaction of 71,4%. (3) There is a causal relationship between the factors of CRM, TQM and service quality implementation with a moderate level.